A Smart Flexible Zinc Battery with Cooling Recovery Ability. (6th June 2017) - Zhao, Jingwen; Sonigara, Keval K.; Li, Jiajia; Zhang, Jian; Chen, Bingbing; Zhang, Jianjun; Soni, Saurabh S.; Zhou, Xinhong; Cui, Guanglei; Chen, Liquan
Abstract: Flexible batteries are essential for wearable electronic devices. To meet practical applications, they need to be mechanically robust and stable. However, strong or multiple bending may sever the interfacial contact between electrode and electrolyte, causing capacity fading or even battery failure. Herein we present a new cooling‐recovery concept for flexible batteries, which involves a temperature‐sensitive sol–gel transition behavior of the thermoreversible polymer hydrogel electrolyte. Once a battery has suffered from strong mechanical stresses, a simple cooling process can refresh the electrode–electrolyte interface. The energy‐storage capability can be recovered with a healing efficiency higher than 98 %. It is believed that this study not only offers new valuable insights, but also opens up new perspectives to develop functional wearable devices.